Ensayo teórico-proyectual de un problema «histórico» (ARQUISUR Revista, 2011)
The Casa Paz in Tafí del Valle, Tucumán, built by the architect Hilario Zalba in 1977, represents an interesting example of American modernity. Based on this case, new discussions about the tense relationship between tradition and modernity are provided herein. Kenneth Frampton’s «regionalism», and Paul Ricouer’s thesis concerning the way to become modern by coming back to the origins, are adopted as theoretical models. The concepts of hybridizing, mixture, syncretism and creolization are also explored. This proposal, more than delineating close conclusions, formulates new questions about a problem which is thrown from present time to History: the contemporary oscillation at cultural field between what is global and what is local.
Keywords: architecture; culture; identity; modern; regionalism